Conditions for establishing fin primary cell cultures in a wide range of ray-finned fishes - Cardoso, Adauto Lima [UNESP]; Oliveira, Jordana Inácio Nascimento [UNESP]; Climaco, João Pedro Silva [UNESP]; Venturelli, Natália Bortholazzi [UNESP]; do Nascimento Moreira, Camila [UNESP]; Martins, Cesar [UNESP] (Springer Nature, 2024)
Ray-finned fishes (Actinopterygii) represent the most diverse vertebrate lineage that show extensive variations in physiology, ways of life, and adaptations to marine and freshwater environments, and several species have been established as biological research models. The in vitro culture of cells is fundamental for several fields of biological research, being an alternative for studies that use animals. Hundreds of fish cell lines have been established using specific methods for each cell type and species. Here is described a protocol which can be used commonly for obtaining cell cultures from the caudal fin of a wide range of ray-finned fishes including marine and freshwater species. Conditions for sample collection, microbial disinfection, tissue dissociation, plating and incubation, cryopreservation and thawing, and karyotyping are described in detail. Primary cell cultures were developed for 20 species grouped into 12 different orders. Eleven of these species have been cultivated in vitro for the first time. In the beginning, the fish cell cultures showed different capacities of proliferation among them; however throughout the passages, most cultures began to have a similar proliferation rate. Throughout the passages, it was noticed that cells similar to fibroblasts began to predominate. The great proliferative ability of these cultures reveals their potential to become cell lines. The culture of A. mexicanus, for example, has been proliferating for months and is already in its 65th passage. Moreover, these cell cultures showed conserved diploid chromosome numbers in comparison with in vivo descriptions which suggest these cultures have stable karyotypes. Therefore, these cultures have potential to be used in several fields, such as toxicology, cytogenetics, genomics, pathology, immunology, cellular agriculture, and conservation, and this method has the potential to be expanded to species not yet tested, as well as to other organs.
Keywords: Actinopterygii; Biotechnology; Conservation; Cryopreservation; Fins; Invitromatics